Isolation and identification of flavonoids from avocado leaves (Persea americana Mill) - Mustarichie, Resmi; Runadi, Dudi (Asian Journal of Pharmaceutical Research and Development, 2021)
Leaves of avocado (Persea americana Mill) contains bioactive compounds that can act as natural antioxidants. This study was conducted to isolate and identify the flavonoid compounds of avocado leaves. Research stages includes maceration, fractionation, thin-layer chromatography analysis, isolation and purification of compounds also identification of isolates in two-dimensional thin-layer chromatography and by using three different types of solvents. Isolates were identified using ultraviolet-visible spectrophotometry and infrared spectrophotometry. From the results obtained one isolate FA6 showed a single compound. Based on the results by testing the purity of isolates using two-dimensional thin-layer chromatography and by using three different types of solvents, isolates FA6 is a pure compound. Identification by using ray-visible spectrophotometry FA6 isolates showed maximum wavelength at 280.6 nm and 342.0 nm on bands II and on band I. Infrared spectrum ofisolate FA6 showed aromatic OH groups, aliphatic CH, C = O stretching, C = C aromatic, and C-O-C stretch. From the results obtained isolates FA6 is a class of flavonoids group flavones or flavonol (3-OH substitional).